2018
DOI: 10.1136/heartjnl-2017-312793
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive perventricular versus open surgical ventricular septal defect closure in infants and children: a randomised clinical trial

Abstract: NCT02794584 ;Results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
20

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 28 publications
2
23
0
20
Order By: Relevance
“…Transthoracic device closure of ventricular septal defect (VSD) in children, which combines the advantages of surgical repair and transcatheter device closure of VSD, has been widely used in the clinic in recent years, especially in China [ 1 , 2 ] . The technique has the advantages of a small incision, without the need for cardiopulmonary bypass, a simple operation process and quick recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Transthoracic device closure of ventricular septal defect (VSD) in children, which combines the advantages of surgical repair and transcatheter device closure of VSD, has been widely used in the clinic in recent years, especially in China [ 1 , 2 ] . The technique has the advantages of a small incision, without the need for cardiopulmonary bypass, a simple operation process and quick recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, authors from Guangzhou reported an alternative method using minimal mid-partial sternotomy in 13 patients (22). Minimally invasive perventricular closure of doubly committed subarterial VSD was also reported, but this technique lacks of long term follow-up results (2). In our opinion, surgical closure from LALT is preferred in such patient groups.…”
Section: Discussionmentioning
confidence: 89%
“…Liu H et al conducted an open-label randomised controlled trial comparing the traditional open surgical approach to the new minimally invasive periventricular approach. 10 This study found that…”
Section: Indications For Repair Of Vsdmentioning
confidence: 90%